Alpha-ketoglutarate affects murine embryo development through metabolic and epigenetic modulations. Issue 2 (August 2019) - Zhang, Zhenzhen; He, Changjiu; Zhang, Lu; Zhu, Tianqi; Lv, Dongying; Li, Guangdong; Song, Yukun; Wang, Jing; Wu, Hao; Ji, Pengyun; Liu, Guoshi
Abstract : α-Ketoglutarate (α-KG) is an intermediary metabolite in the tricarboxylic acid (TCA) cycle and functions to inhibit ATPase and maintain the pluripotency of embryonic stem cells (ESCs); however, little is known regarding the effects of α-KG on the development of preimplantation embryos. Herein, we report that α-KG (150 μM) treatment significantly promoted the blastocyst rate, the number of inner cell mass (ICM) cells and foetal growth after embryo transfer. Mechanistic studies revealed two important pathways involved in the α-KG effects on embryo development. First, α-KG modulates mitochondria function by inducing relatively low ATP production without modification of mitochondrial copy number. The relatively low energy metabolism preserves the pluripotency and competence of the ICM. Second, α-KG modifies epigenetics in embryos cultured in vitro by affecting the activity of the DNA demethylation enzyme TET and the DNA methylation gene Dnmt3a to increase the ratio of 5hmC/5mC ratio. Elevation of the 5hmC/5mC ratio not only promotes the pluripotency of the ICM but also leads to a methylation level in an in vitro embryo close to that in an in vivo embryo. All these functions of α-KG collectively contribute to an increase in the number of ICM cells, leading to greater adaptation of cultured embryos to in vitro conditions and promoting foetal growth after embryo transfer. Our findings provide basic knowledge regarding the mechanisms by which α-KG affects embryo development and cell differentiation.